Sediment analyses of sediment core M157_12-17 - Florian Scholz; Paul Vosteen; Matthias Zabel (PANGAEA, 2022)
Particulate organic carbon (POC), total particulate nitrogen (TN) and total particulate sulfur (TS) were determined by using an element analyzer (Euro EA, HEKAtech). POC was determined after acidifying the sample with 0.25N HCl to remove carbonate. POC content refers to the dry weight percent (wt %) of C (detection limit <0.1 wt% and relative error of 3%). Total iron (TFe) concentrations in the solid phase was determined by ICP-OES following digestion in nitric acid, hydrofluoric acid and perchloric acid. Porosity was determined from the water loss after freeze-drying assuming a seawater density of 1.023 g cm-3 and a particle density of 2.5 g cm-3.